Respuestas
Respuesta dada por:
1
Respuesta:
(3c + 2a) (8a - 2c)
3x + 2y = (36c + 24a) × (8a - 2c)
3x + 2y = 288ca - 72c² + 192a² - 48ac
3x + 2y = 240ca - 72c² + 192a²
3x + 240ca - 72c² + 192a² - 2y
x = 80ca - 24c² + 64a² - ⅔y
Respuesta dada por:
1
Respuesta:
(3c + 2a) (8a - 2c)
Multiplique los paréntesis
3cx 8a - 3c o 2c + 2ax 8a - 2ax2c
Calcule
24ac - 6c+ 16 a- 4ac
Agrupe los términos semejantes
Solución
20ac - 6c + 16a
Preguntas similares
hace 3 años
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 8 años
hace 8 años